Much more give than take: South Africa as a major donor but infrequent recipient of invasive non‐native grasses - Vernon Visser; John R. U. Wilson; Lyn Fish; Carly Brown; Garry D. Cook; David M. Richardson (Global Ecology and Biogeography, 2016)
Aim Some regions donate more invaders from particular taxonomic and functional groups than they receive. We demonstrate a particularly striking donor–recipient asymmetry in invasion ecology in grasses. Specifically, we explore whether low numbers of invasive grasses in South Africa can be explained by sampling biases, introduction dynamics, species traits or invasibility of ecosystems. Location South Africa, Australia, Chile, Europe and the USA. Methods We tested for a donor–recipient asymmetry using lists of native and non‐native grasses in five regions across the globe. Then, using distribution, trait and environmental data, we tested whether regions differed in: (1) herbarium sampling effort; (2) introduction dynamics of non‐native grasses (primary uses, area of origin and minimum residence time of non‐native grasses); (3) traits of native and non‐native grasses (leaf size, height, life history, growth form, C 3 :C 4 ratio and taxonomic placement); and (4) fire frequency. Results South Africa has fewer invasive grasses, and fewer widespread invasive grasses, than other regions; while grasses native to South Africa are much more likely to be invasive elsewhere than other grasses. This asymmetry cannot be explained by sampling biases, historical trade links or minimum residence time. Rather it is likely to be due to a combination of: (1) the massive scale of the introduction of South African grasses around the world; (2) specific traits that make South African grasses successful competitors; and (3) the high fire frequency of many South African ecosystems to which many native grasses are adapted, but introduced grasses are not. Main conclusion South Africa has a high diversity of grasses that possess specific traits to cope with fire, grazing and disturbance. This makes them more competitive. Moreover, the high diversity of certain grass lineages in South Africa acts as a reservoir of potential invaders and possibly helps limit invasions in South Africa by promoting fire.

Mineral nutrition and specific leaf area of plants under contrasting long-term fire frequencies: a case study in a mesic savanna in Australia - Marcelo Claro de Souza; Davi Rodrigo Rossatto; Garry David Cook; Ryosuke Fujinuma; Neal William Menzies; Leonor Patricia Cerdeira Morellato; Gustavo Habermann (Trees, 2016)

Buffel grass and climate change: a framework for projecting invasive species distributions when data are scarce - Tara G. Martin; Helen Murphy; Adam Liedloff; Colette Thomas; Iadine Chadès; Garry Cook; Rod Fensham; John McIvor; Rieks D. van Klinken (Biological Invasions, 2015)

Natural abundance (δ15N) indicates shifts in nitrogen relations of woody taxa along a savanna–woodland continental rainfall gradient - Fiona M. Soper; Anna E. Richards; Ilyas Siddique; Marcos P. M. Aidar; Garry D. Cook; Lindsay B. Hutley; Nicole Robinson; Susanne Schmidt (Oecologia, 2015)

The number of days on which increment occurs is the primary determinant of annual ring width in Callitris intratropica - David M. Drew; Anna E. Richards; Garry D. Cook; Geoffrey M. Downes; Warwick Gill; Patrick J. Baker (Trees, 2014)

The Importance of Termites to the CH4 Balance of a Tropical Savanna Woodland of Northern Australia - Hiz Jamali; Stephen J. Livesley; Samantha P. Grover; Tracy Z. Dawes; Lindsay B. Hutley; Garry D. Cook; Stefan K. Arndt (Ecosystems, 2011)

Optimal Fire Regimes for Soil Carbon Storage in Tropical Savannas of Northern Australia - Anna E. Richards; Garry D. Cook; Brian T. Lynch (Ecosystems, 2011)

Spatial variation in the duration of the rainy season in monsoonal Australia - Garry D. Cook; Richard G. Heerdegen (International Journal of Climatology, 2001)
Climatological research in the tropics of northern Australia has focused particularly on the Australian summer monsoon. However, the timing of many ecologically important processes is determined not by the monsoon but by extra‐monsoonal rainfall events. These events produce a temporal pattern of wet and dry spells that is at least as important ecologically as the amount of rain. We defined the rainy season as that period when the probability of 10‐day dry spells was less than 0.5, and the wet season as that period within the rainy season when the probability of dry spells was less than 0.1. We applied these criteria to seven stations along a strong north–south rainfall gradient spanning more than 12° of latitude in tropical north Australia. The duration of the rainy and wet seasons in northern Australia decreases with increasing latitude. The timing and duration of these seasons were also affected by the El Niño–Southern Oscillation (ENSO). The relative contribution of temporally isolated rainfall events to both the duration of the rainy season and the amount of rainfall increases with latitude. The geographic variation in these seasons corresponds to many patterns occurring in natural ecosystems. We argue that understanding the extra‐monsoon rainfall events is critical to understanding how climate variation affects natural ecosystems. Copyright © 2001 Royal Meteorological Society